Staying in touch with the community: understanding self-reported health and research priorities in older Aboriginal Australians. (21st November 2020) - Lavrencic, Louise M.; Mack, Holly A.; Daylight, Gail; Wall, Sharon; Anderson, Margaret; Hoskins, Sue; Hindman, Emily; Broe, Gerald A.; Radford, Kylie
ABSTRACT: Objectives: Aboriginal Australians experience higher rates of non-communicable chronic disease, injury, dementia, and mortality than non-Aboriginal Australians. Self-reported health is a holistic measure and may fit well with Aboriginal views of health and well-being. This study aimed to identify predictors of self-reported health in older Aboriginal Australians and determine acceptable research methodologies for future aging research. Design: Longitudinal, population-based study. Setting: Five communities across New South Wales, Australia (two urban and three regional sites). Participants: Aboriginal and Torres Strait Islander people ( n = 227; 60–88 years, M = 66.06, SD = 5.85; 145 female). Measurements: Participants completed baseline (demographic, medical, cognitive, mental health, and social factors) and follow-up assessments (self-reported health quantified with 5-point scale; sharing thoughts on areas important for future research). Predictors of self-reported health were examined using logistic regression analyses. Results: Self-reported health was associated with sex, activities of daily living, social activity participation, resilience, alcohol use, kidney problems, arthritis, falls, and recent hospitalization. Arthritis, kidney problems, and resilience remained significant in multiple logistic regression models. Conclusions: Perceived resilience and the absence of certain chronic age-related conditions predict older Aboriginal peoples' self-reported health. Understanding these factors could inform interventions to improve well-being. Findings on acceptable research methodologies suggest that many older Aboriginal people would embrace a range of methodologies within long-standing research partnerships, which is an important consideration for Indigenous population research internationally.